VALIDASI EMPIRIS MODEL DEEP LEARNING INTEGRATIF TRANSENDEN (MDLIT): REKONSTRUKSI EPISTEMOLOGI TAUHIDIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Hadiyanto; Irawan; Opik Taupik Kurahman; Erni Haryanti (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2026)
This study aims to empirically validate the Model of Deep Learning Integrative-Transcendence (MDLIT) as a conceptual innovation within the philosophy of Islamic education grounded in tauhidic epistemology. The model reconstructs the Deep Learning trilogy—Mindful, Meaningful, and Joyful Learning—into three spiritual dimensions: muraqabah (spiritual consciousness), ḥikmah (epistemological wisdom), and saʿādah (true happiness). Employing an exploratory–transcendental mixed-methods approach, the research integrates philosophical–conceptual analysis with empirical validation conducted at SMP Negeri 52 Bandung. Data were collected through document analysis, classroom observations, student perception questionnaires, and teacher interviews, and analyzed using descriptive and philosophical reflection. The findings indicate that Mindful–Meaningful–Joyful Learning principles were partially implemented, with an average perception score of 4.05 (“good”), showing increased student spiritual awareness and learning joy. Theoretical synthesis reveals that MDLIT embodies the integration of three core pillars of Islamic education: Haryanti’s tauhidic epistemology, Kurrahman’s epistemic adab, and Irawan’s learning with conscience. Philosophically, MDLIT demonstrates initial validity as a transcendental learning model that unites ontological (muraqabah), epistemological (ḥikmah), and axiological (saʿādah) dimensions, aiming to form the Insān Kāmil—a human being who thinks with adab, learns with the heart, and rejoices in faith.